" Measuring the competitive performance of the National Insurance Company and some of its branches using the Revealed comparative advantage index RCAI " (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research dealt with the subject of measuring the competitive performance of the National Insurance Company and some of its branches (Basra, Ninwa, Kirkuk and Babil), Depending on the Revenue Growth Index at the activity level, and the Revealed Comparative Advantage Index RCAIAt the branch level,To measure the competitiveness of the company And some branches, As the problem of research in the lack of adoption by some companies in the insurance service sector on scientific indicators to measure their competitive performance, The aims of the research is to measure the competitiveness of the National Insurance Company, as well as the competitiveness of its branches according to the scientific method, One of the main Conclusions of the research is that the company and branches have a competitive strength at the company level on the one hand, and at the level of the insurance sector on the other hand,The most important recommendations were activating compulsory insurance activity in all branches of the company, Because of its impact on increasing the revenues and competitive strength of the company and its branches at the level of the insurance sector in Iraq .